Formation of Industrial Design Culture from Educational to Professional Life - Hatunoglu, Dogan Can; Kaygan, Pınar (Design and Technology Education: An International Journal, 2024)
Although the professional culture of designers has been emphasized as a peripheral issue in various fields of study in design, such as design culture and design management, it has rarely been the central topic of research. However, studies from other professional fields have demonstrated the significance of studying professional culture, especially its formation in higher educational contexts, as it has direct implications on professional status and career prospects of these professions' members. This paper aims to redress this gap by exploring how the professional culture acquired in industrial design education shapes industrial designers’ work experiences in manufacturing companies? It focuses on the context of Turkey and empirically draws on interviews with industrial designers who have work experience in large-scale manufacturing companies. Interviews reveal insights into industrial designers’ perceptions of the profession, experiences in undergraduate education, adaptations to professional life, and professional experiences in manufacturing companies where they collaborate with other professions, where cultural disconnect becomes visible. The qualitative data analysis highlighted the significance of being a community and having flexibility in space and time in industrial design’s professional culture in the examined context. The findings underline collaboration and teaching of soft skills such as communication and teamwork as implications for industrial design education.